Learn R: As a Language, 2nd ed.: Pedro J. Aphalo, Boca Raton, FL: Chapman & Hall/CRC Press, 2024, xvii + 447 pp., $220.00(H), ISBN: 978-1-032-51843-5. - Yu, Haihan (American Statistician, 2025)
The article focuses on "Learn R: As a Language, Second Edition," a comprehensive guide to R programming by Pedro J. Aphalo. This book serves as an introductory resource for those new to R, emphasizing the mastery of the language itself rather than specific data analysis tasks. It includes numerous example codes, updates reflecting the latest changes in R, and a unique open-access R package, learnrbook, which enhances accessibility. The text is structured to provide a thorough understanding of R's fundamental concepts, making it suitable for both beginners and those looking to deepen their programming skills.